Pengaruh Profitabilitas, Leverage dan Likuiditas terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Suci Ramayani Br Margolang; Nisfu Fhitri (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the effect of profitability, leverage, and liquidity on firm value in property and real estate companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The main issue addressed in this research is the inconsistency of previous findings regarding the determinants of firm value in the property and real estate sector. Firm value is measured using Price to Book Value (PBV), while profitability, leverage, and liquidity are proxied by Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR). This research applied a quantitative approach with descriptive methods using secondary data obtained from annual financial reports. The sampling technique employed purposive sampling, resulting in 11 companies with 33 observations. Data analysis was conducted using multiple linear regression assisted by SPSS software and supported by classical assumption tests. The results indicate that simultaneously ROA, DER, and CR do not significantly affect PBV. Partially, ROA has a significant negative effect on PBV, while DER and CR do not show a significant effect on firm value. The findings suggest that investors in the property and real estate sector consider factors beyond financial ratios in assessing company value.